Bioenergy Recovery from Anaerobic Co-Digestion of Crude Glycerol and Domestic Sewage In-Series Reactor: Microbial Characterization and System Performance - Adames, Luan Vieira [UNESP]; Jacobus, Ana Paula [UNESP]; Sakamoto, Isabel Kimiko; Lazaro, Carolina Zampol; Pires, Lorena Oliveira [UNESP]; Maintinguer, Sandra Imaculada [UNESP] (Springer Nature, 2022)
Experiments in series horizontal anaerobic reactors with fixed bed (HARFB) were conducted to evaluate the co-digestion of crude glycerol (CG) from biodiesel production and domestic sewage (DS) concerning the start-up strategy and best organic loading rate (OLR) to improve biogas production as well as to analyze the dynamic changes in the anaerobic microbial consortium during their operation. This approach can be used to increase the buffering capacity of anaerobic reactors as well as dilute toxic compounds. The reactor configuration applied at the present research is a novelty about CG and DS co-digestion and biogas production. The highest hydrogen generation was 10.3 mol H2 (m3 day−1) in reactor R1, and the highest methane yield was 312.0 and 283.9 L CH4 (m3 day−1) in R2 and R3, respectively. These values, obtained with mixed culture, agree with previous co-digestion research. The three-stage system showed high efficiency in removing crude glycerol and chemical oxygen demand (COD), with consumptions of 99.9%, both. The strategy of co-digestion is positive to avoid substrate inhibition. In addition, there was a change in the relative abundance of microorganisms among R1, R2, and R3 and a considerable decrease in the diversity index in the fermentation reactor (R1). The results have shown the potential of applying HARFB reactors for energy recovery and alternative waste disposal. Graphical abstract: [Figure not available: see fulltext.].
Keywords: Biodiesel; Bioenergy; Co-digestion; Domestic sewage; PCR-DGGE